Multiobjective optimization of 3-DOF magnetic bearing considering eddy current effects and saturation. (1st January 2023) - Yu, Chunmin; Deng, Zhiquan; Mei, Lei; Peng, Cong; Cao, Xin
Abstract: The multiobjective optimization method of three-degrees-of-freedom hybrid magnetic bearings (3-DOF HMBs) is crucial compared to time-consuming finite element calculation due to their three dimensional magnetic field. Solid rotors are the first choice for high-speed applications because the yield strength of laminated rotors is lower. However, solid materials may induce eddy current effects and saturation problems. In addition, a 3-DOF HMB has solid and laminated materials and permanent magnet materials, and the material price presents a risk for the structure. In view of the above mentioned problems, a dynamic magnetic circuit model of the 3-DOF HMB with eddy current and saturation effects is initial given. Subsequently, a multiobjective optimization design method for maximum axial and radial bearing capacity and the lowest cost is proposed. Finally, the optimized parameters are given, and a prototype is manufactured. The range of all optimal solutions considering saturation is less than that without saturation, and the maximum reduction is 99%. The experimental results demonstrate the effectiveness of the optimized design results.